2023
DOI: 10.3389/fnimg.2022.1098604
|View full text |Cite
|
Sign up to set email alerts
|

A standardized protocol for manually segmenting stroke lesions on high-resolution T1-weighted MR images

Abstract: Although automated methods for stroke lesion segmentation exist, many researchers still rely on manual segmentation as the gold standard. Our detailed, standardized protocol for stroke lesion tracing on high-resolution 3D T1-weighted (T1w) magnetic resonance imaging (MRI) has been used to trace over 1,300 stroke MRI. In the current study, we describe the protocol, including a step-by-step method utilized for training multiple individuals to trace lesions (“tracers”) in a consistent manner and suggestions for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Although data for this study came from different sites, manual stroke lesion drawings were performed at a single center with standardized protocols. 23 Moreover, we have previously demonstrated that our automated WMH segmentation protocol is robust across multiple sites in individuals with stroke. 24 Future work could make use of advanced imaging metrics such as diffusion tensor imaging to capture more sensitive quantitative information about the white matter structure in cerebrovascular disease 43 and provide further insight into specific damage in patients with poor recovery.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Although data for this study came from different sites, manual stroke lesion drawings were performed at a single center with standardized protocols. 23 Moreover, we have previously demonstrated that our automated WMH segmentation protocol is robust across multiple sites in individuals with stroke. 24 Future work could make use of advanced imaging metrics such as diffusion tensor imaging to capture more sensitive quantitative information about the white matter structure in cerebrovascular disease 43 and provide further insight into specific damage in patients with poor recovery.…”
Section: Discussionmentioning
confidence: 88%
“…Stroke lesions were manually traced on T1-weighted scans by trained researchers following established ENIGMA lesion tracing protocols. 22 , 23 WMH damage was operationalized by whole-brain WMH volume. WMH volumes were segmented with Freesurfer's SAMSEG, which we previously established has robust performance in multisite data from individuals with stroke.…”
Section: Methodsmentioning
confidence: 99%
“…Though data for this study came from different sites, manual stroke lesion drawings were performed at a single center with standardized protocols. (Lo et al ., 2023) Moreover, we have previously demonstrated that our automated WMH segmentation protocol is robust across multiple sites in individuals with stroke. (Ferris et al ., 2023) A limitation of the multisite and secondary nature of our study sample is that we had limited availability of additional covariates that may influence WMH severity and stroke outcomes, most notably cardiometabolic risk factors such as diabetes and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke lesions were manually traced on T1-weighted scans by trained researchers following established ENIGMA lesion tracing protocols. (Liew et al ., 2018; Lo et al ., 2023) WMHs were segmented with Freesurfer’s SAMSEG, which we previously established has robust performance in multi-site data from individuals with stroke. (Ferris et al ., 2023) Linearly co-registered T1 and FLAIR/T2 scans were used as inputs into SAMSEG, and a 0.1 probability threshold was applied to tissue segmentation.…”
Section: Methodsmentioning
confidence: 99%